Seeing is believing? approaches to visual research - Pole, Christopher J. (Christopher John), 1959- (Studies in qualitative methodology ;, 2004)
Recent years have seen an increase in the use of visual methods of research across the social sciences. As researchers realize the potential of the visual, not only as a source but also as a means of generating data, a range of techniques has been developed which seek data that are different from those offered by more conventional qualitative research methods. The contributions to this collection start from the premise either that visual research allows a view of the social world which is not available by other means, or that its use offers a means of augmenting other methods, such as discussion and interview. Rather than providing a step-by-step guide to the use of visual methods, the various authors draw on their experience of visual research to provide critical and reflexive accounts of its use in the field, its potential for unlocking otherwise unseen places, spaces and social action and as a basis for the generation of conceptual and theoretical insight.